Circulating Endothelin-1 as a Diagnostic Marker in Patients with Acute Myocardial Infarction: A Cross-sectional Study - Anitha Rajendiran; S Sumathi; S Giridharan; V Kuzhandaivelu (Journal of Clinical and Diagnostic Research, 2025)
Introduction: The most common form of Coronary Heart Disease (CHD) is Acute Myocardial Infarction (AMI). When a coronary artery is blocked, it results in a substantial reduction in blood flow, which causes some of the heart muscle supplied by that artery to become infarcted. The development of Myocardial Infarction (MI) is regulated by a variety of complex processes. Vascular blockage and cardiac ischaemia may be exacerbated by endothelial dysfunction, platelet activation, and inflammation. Aim: To investigate the potential role of Endothelin-1 (ET-1) in the diagnosis of AMI. Materials and Methods: This cross-sectional research was carried out at Mahatma Gandhi Medical College and Research Institute in Pondicherry, India over the duration of one year (2023-2024) with a sample size of n=50 for the AMI group and n=30 for the healthy control group. Ethical clearance was obtained prior to the study. Upon admission, a 5 mL sample of peripheral venous blood was collected, centrifuged, and biochemical parameters such as glucose (random), urea, creatinine, and lipid profile were assessed using standard appropriate methods. The Enzyme-Linked Fluorescence Assay (ELFA) method was used to test troponin I, and the ET-1 immunoassay ELISA kit was utilised to quantify ET-1. Data were recorded and analysed using Statistical Package for Social Science (SPSS) Version 23 software. Categorical variables were analysed using the Chi-square test, whereas non-normally distributed continuous data were assessed with the Mann-Whitney U test. A Receiver Operating Characteristic (ROC) curve was plotted to identify the optimal cut-off value for ET-1 levels in patients with AMI. Bivariate correlation analysis was performed using the Spearman correlation test. Results: Serum ET-1 levels were significantly higher in AMI subjects compared to the control group (14.02±12.2 pg/mL vs. 3.1±2.8 pg/mL, p<0.001). The ROC curve analysis indicated that the serum ET-1 cut-off level was found to be 6.1 pg/mL. Additionally, serum ET-1 levels showed significant correlations with troponin I levels (correlation coefficient: 0.513, p=0.001). Conclusion: Elevated serum ET-1 levels at the time of admission were associated with higher troponin-I levels in patients with AMI. Hence, ET-1 can be a promising diagnostic marker for AMI assisting in early detection and prognosis.